Fatty Acid Esters from Roots of Amaranthus hybridus Linn. - Singh, Sumitra; Singh, Sandeep; Kumar Sharma, Surendra; Ali, Mohammad (Asian Journal of Chemistry, 2010)
New fatty acid esters were isolated from ethanolic extract of roots of Amaranthus hybridus Linn. (Amaranthaceae). The structures of these compounds were established on the basis of the detailed chemical reaction and spectral analysis as 8'-hydroxynonadecanyl-n-decanoate (1), ndocos- 11-enoic acid (2), n-pentacosonyl-n-octadec-9-enoate (3), n-tricosanyl-n-octadec-9,12- dienoate (4).